2003
DOI: 10.1074/jbc.m301525200
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor α, a Molecular Switch Converting Transforming Growth Factor-α-mediated Proliferation into Differentiation in Neuroblastoma Cells

Abstract: Transforming growth factor-␣ (TGF-␣) is known to promote both proliferation and differentiation of neural cell progenitors. Using the human neuroblastoma cell line SK-N-BE that is induced to proliferate by TGF-␣, we demonstrated that the expression of a single transcription factor, the estrogen receptor-␣ (ER␣), can reroute the TGF-␣ mitogenic signaling toward a path leading to differentiation. With selected mutations in ER␣ and signal transducer and activator of transcription 3 (Stat3), we demonstrated that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
15
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 48 publications
6
15
0
Order By: Relevance
“…In order to clarify the regulation of Hes-1 during mitogenic stimulation of neuroblastoma cells, we treated SK-N-BE(2)c cells with the EGFR ligand TGFa. In line with data published by other groups [27], we found a growth-promoting effect of TGFa, detected already at 24 h and maintained after 48 h in culture ( Figs. 1a and b).…”
Section: Tgfa Stimulation Promotes Growth Of Neuroblastoma Cells and supporting
confidence: 94%
See 1 more Smart Citation
“…In order to clarify the regulation of Hes-1 during mitogenic stimulation of neuroblastoma cells, we treated SK-N-BE(2)c cells with the EGFR ligand TGFa. In line with data published by other groups [27], we found a growth-promoting effect of TGFa, detected already at 24 h and maintained after 48 h in culture ( Figs. 1a and b).…”
Section: Tgfa Stimulation Promotes Growth Of Neuroblastoma Cells and supporting
confidence: 94%
“…In this report, we have analyzed the link between mitogen-activated protein kinase (MAPK) signaling and Hes-1 regulation by stimulating neuroblastoma cells with the transforming growth factor a (TGFa), which in previous studies have shown to be a mitogen of neuroblastoma cells [27]. We show that Hes-1 expression is directly correlated to the MAPK activity and that this induction is not mediated by increased signaling activity of the Notch receptors.…”
Section: Introductionmentioning
confidence: 90%
“…E2 might still modulate via ERα the activity of other transcription factors including the AP-1 (Webb et al 1995) or Stat (Signal Transducer and Activator of Transcription) proteins (Bjornstrom and Sjoberg 2002). Ciana et al (2003) noted that ERα and Stat3 are functionally interact and are able to prevent TGFα-induced proliferation in the neuroblastoma cell line SK-N-BE. This protein/protein interaction subtracts ER from the binding to the ERE-containing promoters, shifting the cell program toward differentiation .…”
Section: Neuronal Effects Of Estrogensmentioning
confidence: 96%
“…Cells (50 × 10 6 ) were incubated for 5 min in a lysis buffer (10 mM Tris·HCl, pH 7.4, 3 mM MgCl 2 , 0.5% Nonidet P-40, and 10 mM NaCl) and nuclei were pelleted by microfuge centrifugation. Nuclear run-on assays were performed as described (39). Four-h prehybridization and 24-h hybridization were carried on in Church and Gilbert's solution at 72°C; 2 × 10 6 cpm/mL were used in the hybridization reaction.…”
Section: Methodsmentioning
confidence: 99%